Pelatihan peningkatan kompetensi guru SMK Satria dalam melaksanakan pembelajaran saintifik di Kota Jambi - Ekawarna, Ekawarna; Saharudin, Saharudin; Kusmana, Ade; Kristiyono, Santo (Community Empowerment Journal, 2023)
The urgent need for partner teachers (SMK Satria) at this time is "training to improve teacher competence in implementing scientific learning". The training targets of the training program as an effort to improve the quality of the process and student learning outcomes are 24 teachers of SMK Satria, Jambi City, Jambi Province. The expected outputs of the training activities to improve teacher competence in implementing scientific learning are as follows: (a) Increasing teacher competence in the affective domain so that they are able to assess teacher professional development activities in accordance with the guidelines so that the objectives of teacher professional development activities can be achieved; (b) Increasing teacher competence in the psychomotor domain, namely the ability of teachers to practice scientific learning; (c) Increasing teacher competence in the cognitive domain so that they have the competence to know and understand clear reasons and suggestions, and provide learning impacts for improvement for the teacher himself. The material is provided through adult learning methods (andragogy), with a ratio of 30% theory (9 Meeting Hours/JP) and 70% practice (27 Meeting Hours/JP). In adult learning, more emphasis is placed on improving the quality of their lives, providing skills and abilities to solve the problems they experience in life and their service tasks. The overall increase in average competence of trainees as a result of the training reached 62%. The results of the questionnaire on training satisfaction resulted in information that the implementation of the training could satisfy the trainees (average 95%), both in terms of the achievement of training objectives, training methods, instructor quality, time and media used. The recommended suggestion is that local governments need to budget funds for the implementation of advanced Scientific Learning training activities for teachers funded from the Provincial or District / City APBD.